Estimates of the Causal Effects of Education on Earnings over the Life Cycle with Cohort Effects and Endogenous Education. (22nd December 2017) - Migali, Giuseppe; Walker, Ian
Abstract: We estimate the wage premia associated with educational attainments focusing on the life cycle pattern of earnings. We employ a model where educational attainment is discrete and ordered and log wages are determined by a simple function of work experience for each level of attainment. We distinguish between life cycle and cohort effects by exploiting the fact that we have a short panel. We find that age–earnings profiles lose the traditional bell shape and become flat when we allow for cohort differences. Females still have higher college premia compared to males. However, there are clear earnings inequalities between cohorts with smaller college premia for younger compared to older cohorts, for both males and females. (JEL codes: I21, J31, C32)